Does religiosity explain economic outcomes? - Olga Popova (IZA World of Labor, 2017)
Most religions in transition economies were marginalized by their former communist regimes. Today, some of these countries are experiencing a revival of religiosity, while others are prone to secularization. Religious norms affect individual decision making with respect to human capital investment, economic reforms, marital stability, employment, and other contexts. This implies that the interests of both religious and non-religious communities may differ and must be taken into account when designing and implementing economic policies, which is a challenge for policymakers.
Keywords: I15; I31; O17; P36; P52; Z12; 330; religion and religiosity; secularization; economic behavior; transition economies